Compositional differences between the component stars of eclipsing close binary systems showing chemical peculiarities. Issue 1 (14th February 2019) - Takeda, Yoichi; Han, Inwoo; Kang, Dong-Il; Lee, Byeong-Cheol; Kim, Kang-Min
Abstract: A spectroscopic study was carried out on the surface chemical abundances of CNO and several heavier elements in the primary and secondary components of five eclipsing close binaries around A type (AR Aur, β Aur, YZ Cas, WW Aur, and RR Lyn) in order to investigate the nature of chemical differences between both components (being comparatively slow rotators alike due to tidal synchronization). Regarding the systems comprising similar components, β Aur and WW Aur were confirmed to exhibit no compositional difference between the primary and secondary both showing almost the same Am anomaly, though the chemical peculiarities in the component stars of AR Aur show distinct differences (HgMn star and Am star). In contrast, as to the systems (YZ Cas and RR Lyn) consisting of considerably different (A and early F) components, the surface abundances are markedly different between the primary (Am) and secondary (normal). These observational results may indicate T eff -dependent characteristics regarding the chemical anomalies of non-magnetic stars on the upper main sequence: (1) In the effective temperature range of 10 000 K T_eff 7000 K, rotational velocity is the most important factor for determining the extent of Am peculiarity. (2) However, the emergence of the Am phenomenon seems to have a lower T eff limit at ∼7000 K, below which no abundance anomaly is observed regardless of stellar rotation. (3) The transition from Am anomaly (mild deficiency in CNO) to HgMn anomaly (unusually large N depletion) is likely to take place as T eff increases from ∼10 000 K to ∼11 000 K.